Possible Nova in M31 - Hatzidimitriou, D.; Burwitz, V.; Duscha, S.; Kanbach, G.; Pietsch, W.; Reig, P.; Papamastorakis, G. (The Astronomer's Telegram, 2007)
We report the discovery of a possible nova in M31 on four consecutive dithered R filter CCD images obtained on (2007 July 05.04813, 05.04966, 05.05122, 05.05278, with corresponding R magnitudes of 16.7, 16.6, 16.6, 16.6) obtained at the 1.3m Ritchey Chretien f/7.5 telescope at Skinakas Observatory, Crete, Greece, using the Roper CCD Camera (with a SITE 1k x 1k chip with 24Âµm sq. pixels). The position obtained for the nova candidate is RA(2000) = 00h 43m 04.05s, Dec(2000) = +41Â° 17' 08.3" with an accuracy of 0.1".
Keywords: Novae; Optical